The Iran Album (1974): Some Sleeve Notes - Buchanan, Rachel (Archivaria, 2018)
In 1974, feminist writers Germaine Greer, Betty Friedan, and senior United Nations official Helvi Sipila spent six days in Iran. They were invited by Princess Ashraf Pahlavi, the twin sister of the Shah, and the Women’s Association of Iran. The Germaine Greer Archive at the University of Melbourne Archives contains a photograph album that documents this trip. This article uses the Trip to Iran Photograph Album as a case study to demonstrate what Michelle Caswell and Marika Cifor describe as a feminist ethics approach to archival work. It looks at how the creation of detailed metadata can be an act of caregiving and empathy and an opportunity to build – or restore – relationships between objects and the people and places they depict. Original order, ambient knowledge, provenance, conservation, and the powers of social media have helped me give voice (or voices) to this extraordinary archival object. RÉSUMÉ En 1974, les écrivaines féministes Germaine Greer, Betty Friedan et une représentante haut-placée des Nations Unies, Helvi Sipila, passèrent six jours en Iran. Elles avaient été invitées par la princesse Ashraf Pahlavi, la soeur jumelle du Shah, ainsi que par l’Association des femmes de l’Iran. Les archives de Germaine Greer, aux University of Melbourne Archives, contiennent un album de photographies qui documente ce voyage. Cet article se sert de cet album de photographies du voyage en Iran comme étude de cas pour illustrer ce que Michelle Caswell et Marika Cifor décrivent comme une approche éthique féministe envers le travail en archivistique. Il examine comment la création de métadonnées détaillées peut devenir un acte d’aide naturelle et d’empathie, ainsi qu’une occasion de bâtir – ou de rétablir – des liens entre les objets et les personnes et endroits qu’ils dépeignent. L’ordre original, la connaissance contextuelle, la provenance, la préservation et le pouvoir des médias sociaux m’ont aidé à donner une voix (ou des voix) à cet extraordinaire objet d’archives.